Case report: Endoscopic frontal sinus opening surgery for noninflammatory frontal sinus headache: A short case series - Xie, Yan; Wu, Shiqi; Cui, Wanling; Zeng, Dandi; Chen, Feifei; Liang, Fangqi; Lu, Rongrong; Zhang, Chenyu; Jiang, Luyun (Frontiers in Surgery, 2023)
Objective: To analyze rhinogenic headache, i.e. non-inflammatory frontal sinus headache, a headache caused by bony obstruction of the frontal sinus drainage channels that receives relatively insufficient attention clinically, and to propose endoscopic frontal sinus opening surgery as a treatment based on the etiology. Study Design：Case series. Setting：From the data patients with non-inflammatory frontal sinus headache who underwent endoscopic frontal sinus surgery in Hospital of Chengdu University of TCM during 2016 to 2021, three case data with detailed postoperative follow-up data were extracted for case series reports. Methods: This report provides detailed information on three patients with non-inflammatory frontal sinusitis headache. Treatment options include surgery and re-check, the VAS scores of preoperative and postoperative symptom, CT and endoscopic images. Three patients had common characteristics: the clinical manifestations were recurrent or persistent pain and discomfort in the forehead area, but no nasal obstruction or runny nose; the paranasal sinus CT revealed no signs of inflammation in the sinuses, but suggested bony obstruction of the drainage channel of the frontal sinus. Results: Three patients got headache improvement, nasal mucosal recovery, patent frontal sinus drainage. The recurrence rate of forehead tightness and discomfort or pain was 0. Conclusion: Non-inflammatory frontal sinus headache does exist. Endoscopic frontal sinus opening surgery is a feasible treatment modality which can largely or even completely eliminate the stuffy swelling and the pain in the forehead. The diagnosis and surgical indications for this disease are based on a combination of anatomical abnormalities and clinical symptoms.